Mediastinal nonleukemic granulocytic sarcoma with cardiac infiltration - Lima,Gabrielle G. (2008)
We report on a case of mediastinal granulocytic sarcoma with cardiac infiltration in a young man with no evidence of leukemia involving the bone marrow or peripheral blood. Diagnosis was accomplished by immuno-histochemistry with expressions of myeloperoxidase and CD99 antigens. The patient achieved clinical remission, but evolved with febrile neutropenia during chemotherapy and died. Although subclinical cardiac infiltrations are commonly found at autopsy in patients with acute non-lymphoblastic leukemia, only one case of involvement of the heart with granulocytic sarcoma in the absence of bone marrow disease has been published in the literature. A diagnosis of granulocytic sarcoma should not be excluded when the biopsy of the bone marrow does not show any evidence of leukemic infiltration.